Multi-Hollow Surface Dielectric Barrier Discharge for Bacterial Biofilm Decontamination - Zlata Kelar Tučeková; Lukáš Vacek; Richard Krumpolec; Jakub Kelar; Miroslav Zemánek; Mirko Černák; Filip Růžička (Molecules, 2021)
The plasma-activated gas is capable of decontaminating surfaces of different materials in remote distances. The effect of plasma-activated water vapor on Staphylococcus epidermidis, methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli biofilm contamination was investigated on the polypropylene nonwoven textile surface. The robust and technically simple multi-hollow surface dielectric barrier discharge was used as a low-temperature atmospheric plasma source to activate the water-based medium. The germicidal efficiency of short and long-time exposure to plasma-activated water vapor was evaluated by standard microbiological cultivation and fluorescence analysis using a fluorescence multiwell plate reader. The test was repeated in different distances of the contaminated polypropylene nonwoven sample from the surface of the plasma source. The detection of reactive species in plasma-activated gas flow and condensed activated vapor, and thermal and electrical properties of the used plasma source, were measured. The bacterial biofilm decontamination efficiency increased with the exposure time and the plasma source power input. The log reduction of viable biofilm units decreased with the increasing distance from the dielectric surface.